Li–Pd–Rh-D2O electrochemistry experiments at elevated voltage - Carl Gotzmer; Louis F. DeChiaro; Kenneth Conley; Marc Litz; Marshall Millett; Jesse Ewing; Lawrence P. Forsley; Karen J. Long; William A. Wichart; Pamela A. Mosier-Boss; John Sullivan; Efrem Perry Jr; et al. (APL Energy, 2023)
In 2013, the U.S. Navy disclosed an electrochemistry procedure intended to produce MeV-energy nuclear particles, based on eV-energy electrical inputs, which may be indicative of a new scientific phenomenon. This work is based on the 2013 disclosure and shows initial evidence validating the prior claims of nuclear particle generation. Additionally, several variations on the 2013 electrochemical recipe are made in order to find a highly repeatable recipe for future replications by other teams. The experiments described here produced dense collections of tracks in solid-state nuclear track detectors, radio frequency (RF) emissions, and anomalous heat flux, which are indicative of potential nuclear, or unusual chemical, reactions. Experimental results include tracks in solid-state nuclear track detectors similar in size to tracks produced by 4.7 MeV alpha particles on identical detectors exposed to radioactive Th-230; RF pulses up to 6 dB above the noise floor, which indicate that these signals were likely not background noise and not caused by known chemical reactions; and heat flux of 10 s of kJ, measured to 6σ significance, over and above input electrical energy, indicative of unknown exothermic reactions. Six out of six nuclear track detectors, utilized in experiments and interrogated for tracks post-experiment, produced positive results that our team attributes to thousands of individual particle impacts in dense clusters, likely with energies between 0.1 and 20 MeV. Similar nuclear particle, thermal, and RF results have separately appeared in prior reports, but in this work, all three categories of anomalous behavior are reported. Results indicate that the 2013 procedure may be a useful guide toward a set of highly repeatable reference experiments, showing initial but not overwhelming evidence of a new scientific phenomenon. Repeatable recipes are shared so that other groups may replicate and extend the present work.